2011
DOI: 10.1523/jneurosci.6041-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Domain Contacts Is Required for Heterotetrameric Assembly of Functional NMDA Receptors

Abstract: The precise knowledge of the subunit assembly process of NMDA receptors (NMDA-Rs) is essential to understand the receptor architecture and underlying mechanism of channel function. Because NMDA-Rs are obligatory heterotetramers requiring the GluN1 subunit, it is critical to investigate how GluN1 and GluN2 type subunits coassemble into tetramers. By combining approaches in cell biology, biochemistry, single particle electron microscopy, and x-ray crystallography, we report the mechanisms and phenotypes of mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 55 publications
5
79
0
Order By: Relevance
“…4A). This loop adopts different configurations in various GluN1 NTD crystal structures (11,16) and displays high flexibility in molecular dynamic simulations (25). To explore the possible role of I133 in photo-cross-linking, we generated a series of double mutant receptors, mutating I133 to G, A, V, or L on the GluN1-Y109amb background.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4A). This loop adopts different configurations in various GluN1 NTD crystal structures (11,16) and displays high flexibility in molecular dynamic simulations (25). To explore the possible role of I133 in photo-cross-linking, we generated a series of double mutant receptors, mutating I133 to G, A, V, or L on the GluN1-Y109amb background.…”
Section: Resultsmentioning
confidence: 99%
“…1A). Besides having essential functions in receptor assembly (10,11), recent studies of the NTDs have also revealed that the individual GluN2 (12)(13)(14) and GluN1 (15) NTDs fine-tune NMDAR gating and pharmacological properties by undergoing large-range conformational changes. The recent X-ray crystal structure of a GluN1/GluN2B NTD complex reveals a unique arrangement of the two NTD protomers with intersubunit interactions distinct from those observed in AMPA and kainate receptors (16,17).…”
mentioning
confidence: 99%
“…Many studies have confirmed that NTDdriven dimerization is an important early step in the assembly (Refs. 16,18,59; for reviews, see Refs. [63][64][65], and point mutations in the NTD can lead to impaired maturation and surface expression (18,59).…”
Section: Discussionmentioning
confidence: 99%
“…16,18,59; for reviews, see Refs. [63][64][65], and point mutations in the NTD can lead to impaired maturation and surface expression (18,59). Nascent receptor dimers held together by N-terminal dimerization and by transmembrane segment packing, but with clearly separate LBDs, have been identified in an electron microscopic analysis of AMPA receptor biosynthesis (16).…”
Section: Discussionmentioning
confidence: 99%
“…These structural data shed further light on differences between the NMDA receptor ATDs and those of kainate and AMPA receptors. Whereas the ATDs of all ionotropic glutamate receptors have a bilobed architecture and consist of two domains (R1 and R2), NMDA receptors are unique compared with kainate and AMPA receptors in that the R1 and R2 lobes are oriented differently with respect to each other (Karakas et al, 2009(Karakas et al, , 2011Farina et al, 2011). This difference in orientation of the R1 and R2 domains results in distinct association between the GluN1/ GluN2B ATDs that differs in molecular detail from non-NMDA receptor ATDs, which can associate as homodimers or heterodimers (Zhao et al, 2012;Kumar et al, 2009Kumar et al, , 2011 and extensive strong interactions between the R1-R1 and R2-R2 domains of the dimer.…”
Section: Introductionmentioning
confidence: 99%